The U.S. Current Account Deficit and the Global Economy. (per Jacobson lecture, 2004)
This paper presents the views of Lawrence H. Summers on the U.S. current account deficit and the global economy. Summers highlights that the U.S. current account deficit is currently running well in excess of USD 600 billion at an annual rate, in the range of 5.5 percent of GDP. It represents more than 1 percent of global GDP and absorbs close to two-thirds of the cumulative current account surpluses of all the world's surplus countries. Summers thinks that such a unique imbalance deserves careful scrutiny.